PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA POLISI DI POLRES CILACAP - Esih Jayanti; Akhmad Husain Andi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
Human resources are one of the main roles in an organization, including the Indonesian National Police. The higher the ability of the unit member in the Police, the higher its performance. In order for the police performance in the Cilacap Regional Police Station to be consistent and maximal, the organization must pay attention to the factors that can affect a person's ability to carry out their duties and responsibilities such as the application of rewards and punishments. This study aims to examine and analyze the effect of, Reward and Punishment on Police Performance in the Cilacap Regional Police Station. This research method is descriptive quantitative, with purposive sampling technique. The sample in this study were 93 respondents who were police officers at the Cilacap Regional Police Station. To determine the magnitude of the influence of reward, and punishment on police performance, multiple linear regression analysis was used. The F test is used to examine the overall effect between Reward and Punishment with degrees of freedom (df) = k and (n-k-2) with confidence level (α = 0.05). To find out the partial effect, the T test of degrees of freedom (df) = k and (n-k-2) was used with a confidence level (α = 0.05). The results of the test can be concluded that both partially and simultaneously, reward and punishment affect the police performance in the Cilacap Regional Police Station.